Evaluasi Perda No. 5 Tahun 2013 Tentang Penataan Pasar Tradisional, Pusat Perbelanjaan dan Toko Modern (Studi Kasus : Perlindungan dan Pemberdayaan Pasar Tradisional di Kecamatan Sukawati Kabupaten Gianyar) - Apsari, Ni Luh Putu Desi; Pascarani, Ni Nyoman Dewi; Winaya, I Ketut (CITIZEN CHARTER, 2017)
Abstract The existence of modern market rapidly grow and make threaten the existence of traditional markets, its therefore Gianyar Regency Government makes Regulation No. 5 year 2013 about arrangement of the shopping center, modern shops and traditional markets to protect and the empowerment traditional markets. The problem in the background for this research is the arrangement of traditional market condition that is less than the maximum, complaints traditional traders in traditional market because modern market in Sukawati. After that Gianyar regency which has not legally applies the legislation about distance between traditional and modern market, also Gianyar Regency its not explicit arrange the quota of modern market in Sukawati district. Therefore researcher focus on evaluated regulation No. 5 of 2013 about the protection and empowerment of traditional markets. This study uses descriptive qualitative with depth interview to informants. The theory used by researchers is the theory from William Dunn about policy evaluation with four indicators used are effectiveness, responsiveness, efficiency and accuracy. The conclusion of this research of the fourth indicator is regulation No. 5 of 2013 is not maximal to protection and empowerment traditional market. Keywords: Evaluation, Protection, Empowerment, Traditional Market